The Modifikasi Pemanas Tambalan Ban Dalam Berbahan Bakar Bensin - Arief Muliawan; Dedy Daud (Jurnal Teknik Juara Aktif Global Optimis, 2022)
Research has been carried out as well as modification of the heater which is operated to patch a leaky tire. Some of the tire filling methods found among the public are not very environmentally friendly. This study uses an empty fire extinguisher tube that is modified so that it can be used as a fuel reservoir and pressure storage. The purpose of this design and research is to save time on workmanship, cheap and affordable prices in the process of making tools, cheap fuel prices, fuel efficient and environmentally friendly and does not cause pollution. The results of this study prove that from the results of the tool testing carried out, the temperature of the test has been measured at 244-289oC. So it is very effective when working with a time of ± 2-3 minutes, then environmentally friendly and fuel efficient which only requires 1 liter of gasoline for several times of work. So it is highly recommended to people who have a tire repair shop business to be able to change to a new method.